2017
DOI: 10.2214/ajr.16.17517
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Point-of-Care Radiologist-Technologist Communication Tool in a Quality Assurance Program

Abstract: OBJECTIVE We implemented an Image Quality Reporting and Tracking Solution (IQuaRTS), directly linked from the PACS, to improve communication between radiologists and technologists. MATERIALS AND METHODS IQuaRTS launched in May 2015. We compared MRI issues filed in the period before IQuaRTS implementation (May–September 2014) using a manual system with MRI issues filed in the IQuaRTS period (May–September 2015). The unpaired t test was used for analysis. For assessment of overall results in the IQuaRTS period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…As in a prior study [9], we show how a relatively low-cost set of components can be used to create a clinically meaningful tool in a large, multifacility academic medical center. Developed by our radiology informatics team, this tool was composed of an application that queried our RIS, a database, and a web-based user interface.…”
Section: Discussionmentioning
confidence: 87%
“…As in a prior study [9], we show how a relatively low-cost set of components can be used to create a clinically meaningful tool in a large, multifacility academic medical center. Developed by our radiology informatics team, this tool was composed of an application that queried our RIS, a database, and a web-based user interface.…”
Section: Discussionmentioning
confidence: 87%
“…6 With the introduction of digital systems, professional interactions between MITs and radiologists have reduced as images are sent electronically. 20,21 It has been suggested that this reduction in communication regarding image quality may contribute to increasing positioning errors. 22 In our study, exposure factors were found to be within the top three reasons for image rejection in both radiology departments.…”
Section: Discussionmentioning
confidence: 99%
“…Notifications of issues can take several forms, such as emails or pages. In our implementation of this module, we incorporated an open-source ticketing system that was previously implemented in a quality improvement effort (4), whereby a ticket would be filed into the ticketing system through an API call whenever an issue is detected, and where the rules engine within the ticketing system can be configured to send an email to a quality control team member appropriate to the particular examination with the issue.…”
Section: Materials / Methodsmentioning
confidence: 99%
“…Our Error Correction Module utilized features in our PACS (Centricity RA1000, GE Healthcare, Chicago, IL) that permitted an administrator to assign a button, available for all users, that performed context passing of data of the currently-viewed exam (eg. current user, exam accession number) to a web application, a methodology previously described for quality reporting (4) . The web application would display current IAA results from the database, with options to correct those results, and then send the corrected data back to the database.…”
Section: Error Correction Modulementioning
confidence: 99%